Designing Functional Virtual Learning Communities Using the Bola Ola Method - Bolanle A. Olaniran (Knowledge Management & E-Learning: An International Journal, 2011)
This paper explores how social media and the likes of Web 2.0 are gaining ground in e-learning and virtual communities. The paper argues that successful learning in virtual learning communities (VLCs) require cultural sensitivity given that technological tools in these communities were not originally designed for learning. The paper uses the dimensions of cultural variability to identify some of the cultural challenges in VLCs. Subsequently, the Bola Ola method is presented as a way to address cultural challenges and effective use of VLCs. Finally, implications are presented as well.